Effects of sampling time interval on the image offsets of the observed points for Moon-based earth observations. Issue 6 (19th March 2021) - Ye, Hanlin; Zheng, Wei; Guo, Huadong; Liu, Guang; wang, Mingyuan; Guo, Qing
ABSTRACT: Due to the almost hemispheric observational scope of the Moon-based Earth observations, the effects of sampling time interval on the image offsets of the observed points are fundamentally different from the cases of traditional satellite-based platforms. Sampling time intervals will affect the offsets in the full-disc image, while the magnitude of the image offsets is dependent on the spatial resolution. Hence, their relationships merit further investigation. To this end, a novel method to determine the image coordinates based on radius-angle pair expression is proposed. The offsets of the observed points between two adjacent samplings can be calculated and the effects of the sampling time interval on the offsets can be analysed. We found that the magnitude of the image offsets in the x -axis direction is approximately two times larger than that in y -axis direction under the same sampling time interval and the effects of the sampling time interval is related to the observed point's latitude. Further, based on the fact that the maximum offsets occur at the Earth's equator, the detailed calculation of the shortest sampling time interval taken to exceed 1-pixel offset corresponding to different spatial resolutions is carried out. The results described herein can provide guidance for designing sensors for Moon-based Earth observations.